Organic acids and alcohols quantification by HPLC/RID in sugarcane vinasse: analytical method validation and matrix effect assessment. Issue 3 (19th February 2021) - Bernardes, Alan Nascimento; Godoi, Leandro Augusto Gouvêa; Camiloti, Priscila Rosseto; Gomes, Absai da Conceição; Sanchez, Bruna Larissa Sandy; Torres, Ana Paula Rodrigues; Botta, Lívia Silva
ABSTRACT: The composition of sugarcane vinasse varies according to the substrate of alcoholic fermentation, e.g. if it is sugarcane juice and/or molasses. Regardless of the origin, the main organic compounds found in sugarcane vinasse are organic acids, alcohols and a low amount of carbohydrates. To access the organic composition of such wastewater, the present paper describes a high-performance liquid chromatography (HPLC) separation method coupled to a Refractive Index Detector (RID) in order to quantify the organic acids (C1 to C6) and alcohols in sugarcane vinasse. The analysed substances were acetic acid, butyric acid, caproic acid, citric acid, lactic acid, propionic acid, succinic acid, valeric acid, butanol, ethanol, glycerol and methanol. A validation study of the method was performed taking into account the matrix effect exerted by vinasse samples in natura . In conclusion, it was proved that the method is suitable for assessing the organic composition of vinasse: able to separate 12 analytes, with excellent linearity (R 2 > 0.999), with adequate working ranges, high precision (recovery ranging from 83% to 102%), and low matrix effects (<5%).